Pengaruh Laba Akuntansi dan Arus Kas terhadap Return Perusahaan Industri Barang Konsumsi - Kartawati Mardiah; Zulham Al Farizi (Jurusan Akuntansi Politeknik Negeri Pontianak, 2017)
This study aims to examine whether the changes of cash flows and accounting profit, used by investors to make investment decision, reflected in the companies’ stock return. There are four independent variables includes in this study, that is cash flows from operating, investing, and financing activities, as well as accounting profit. The stock return is calculated by using the geometric mean method. This research is a replication of the research of Azilia and Yulius (2012). Multiple regression analysis is used to examine the data on public companies (the consumer goods industry sector) listed in Indonesia Stock Exchange for period 2015-2016. The result reveals that accounting profit disclosure markedly affected the stock return. This implies that investors took into account the publication of accounting profit in their decision making. On the other side, the study cannot prove the association of other independent variables to the stock return.